Normative Judicial Analysis of Dissolution of Political Parties Towards Democratic System in Indonesia - Rifandy Ritonga (International Conference On Law, Business and Governance (ICon-LBG), 2013)
The existence of political parties as a manifestation of the freedom of association is needed in a democracy .However , based on existing practices and regulations , political parties turned out to be dissolved . The dissolution of political parties would have to be done based on laws and regulations,procedures , and legal effect of the dissolution of a political party .The problem of this research is the process of dissolution of political parties in the colonial period up to the period of reform in Indonesia and the impact of the dissolution of political parties in Indonesia against the democratic system in Indonesia.This research method is normative, using secondary data obtained from the literature ( library research) , historical studies and data analysis .Dissolution of political parties differ each period, in the period before the reform dissolution of political parties without a clear legal mechanism, unlike the case with the reform era to the present arrangements concerning the dissolution of political parties is clearly stipulated in the Constitution of the Republic of Indonesia Year 1945 , the Article 24C one of the authorities of the Constitutional Court is to decide on the dissolution of political parties , more clearly set out in the judicial procedure in the dissolution of political parties of the Constitutional Court of the Republic of Indonesia Number . 12 of 2008 . Effect of dissolution of political parties into the democratic system in Indonesia did not have an impact on the democratic system that applied in Indonesia. Because dissolution of political parties will only be done if a partyPolitical conflict with the fundamental purpose and the constitutional order . Even more than that on the dissolution of a political party that opposed the aim to protect democracy itself , constitution , national sovereignty , national security and national ideology .Arrangements should political parties in the future will better ensure and protect the freedom of association , assembly , opinion and expression . And its not just the government that granted the privilege to be able to apply for dissolution of political parties , but also citizens are given the same rights to dimiss political parties and threatens harm the state constitution.